Perception of Stakeholders on the Compliance of Sports Facilities to Relevant Standards in Selected Universities in South West Nigeria - Oseghale, Godwin Ehis; Ikpo, Ime Johnson (European Scientific Journal, ESJ, 2018)
This paper examines the level of compliance of sports facilities, in selected universities in South-Western Nigeria to relevant standards (National and International standards). Data were collected using a structured questionnaire which was administered on sports men and women (4 male, 2 female). Personnel responsible for maintenance of sports facilities in the universities were also sampled (two groundsmen from each University, the Director of Sports and two other members of the sport Council, Director of Works, four maintenance Supervisors, and two maintenance administrative staff, and eighteen maintenance operatives in each of the selected University). The study incorporated all the fifteen sports featured at the Nigeria University Games Association (NUGA) competitions. Three federal universities were purposively selected because these have facilities for all the fifteen sports and have hosted national and international sporting events. A total of four hundred and fifty four copies of the questionnaires (454) were administered and (342) copies were retrieved and found useful for analysis. Two hundred and sixty one copies (71.7%) copies of questionnaire were retrieved from sports men and women and 81 copies (90%) from maintenance staff in the universities sampled. Data obtained were analysed using frequency distribution, percentages and mean response analysis. The findings revealed that football field; hockey and cricket pitches were rated very low on the availability of sprinklers. The hard courts were rated very low on ‘crack free’ and ‘free of holes. The swimming pool was equally rated very poorly on pool chemical balance and cleanliness of water. The study concluded that sports facilities in South West Nigeria were not complying with the requisite national and international standards. The study therefore recommended immediate response from the management of the sports facilities in order to return the facilities to normal operations halt accelerated deterioration, correct cited safety hazards and life safety code violations.